The metal content of generic orthodontic brackets compared with proprietary brackets - Wishney Morgan; Savage Tom; Proschogo Nicholas; Petocz Peter; Darendeliler M. Ali (Sciendo, 2018)
With minimal manufacturer information, a variety of 'generic' orthodontic brackets are available online from overseas distributors. The present study investigated the metal composition of generic orthodontic brackets compared with two well-known 'proprietary' brands.